Evaluating Law Teaching: Towards the Improvement of Teaching or Performance Assessment? - Richard Johnstone (Legal Education Review)
In the last few years there has been a move towards assessing and appraising the quality of teaching in Australian universities. While some law schools have on their own initiative paid more attention to this process, in others the issue has arisen in the context of the move towards staff assessment and appraisal which developed out of the second tier National Wage negotiations in the tertiary education sector in 1988. Until these developments, there had been little or no attempt to scrutinise teaching within law schools. It has been commonly accepted that where teaching has been scrutinised for the purposes of promotion, confirmation and recruitment, scrutiny was often based on rumour, innuendo and hearsay. In this context, then, the move towards more rigorous scrutiny of teaching in law schools should be welcome. Of course, there are arguments for and against more rigorous scrutiny of teaching. Why should teaching be ignored or paid lipservice in selection, confirmation and promotion when it is an important and time consuming component of the work of academics in law schools? If teaching is important, it should be taken seriously in recruitment and promotion. This means scrutinising it carefully and fairly. If, as seems likely, academics working in law schools in the 1990s will become much more accountable for their teaching, we had better get used to the idea of teaching being more rigorously scrutinised. This, however, raises a problem of vertical equity. Why should today’s new teachers have their teaching rigorously examined when in the past teaching was largely ignored and, where it was scrutinised, this was done in a far less rigorous fashion than the assessment of research? It is often argued that scrutinisation of teaching is difficult to do, and therefore should not be attempted. It is this last point that this article seeks partly to address. More particularly, this article examines why and how teaching should be scrutinised. The purpose of the process of scrutinising teaching is often overlooked. It is the purpose of this article to suggest that there are at least three major reasons for these processes: evaluation, assessment and staff appraisal and that they should be separated, with different methods used for each.